(untitled) (Human Factors in Design, 2021)
This study aims to identify and analyze research that approaches teleworking in the home office modality and the main implications in the experience during the use of these spaces through a systematic literature review. A set of articles were selected and analyzed which aspects of the experience were considered and which are the main problems in these spaces. It was possible to observe during the review, that a large part of the research found, which deals with teleworking, usually, do it refers to the activity and not to the workstation. Besides, some aspects evaluated are related to satisfaction and well-being, in general, and referring to psychosocial problems, stress, and burnout. The results point there is a lack of research on the physical ergonomics environment and musculoskeletal disease.